The Relationship between Future Time Perspective, Self-Efficacy, and Self-Regulation on Online Learning Engagement - Fajrin, Resti; Sunawan, Sunawan; Mulawarman, Mulawarman (Jurnal Bimbingan Konseling, 2021)
The COVID-19 pandemic urges students to do online learning. However, many were found to have low learning engagement during this condition. Thus, this study intended to examine the effects of Future Time Perspective (FTP), self-efficacy, and self-regulation on online learning engagement. 400 Islamic Senior High School or SMA Islam students in Semarang City participated in this correlational study. Findings showed that there was a positive relationship between future time perspective and self-efficacy on online learning engagement. Unfortunately, self-regulation did not predict the online learning engagement significantly. It indicates that in online learning during the COVID-19 pandemic, students have less control over their learning activities.